Non-allergist healthcare workers views on delivering a penicillin allergy de-labelling inpatient pathway: identifying the barriers and enablers - Powell, N; Upton, M; Kent, B; Sandoe, J; Tonkin-Crine, S (Oxford University Press, 2024)
Background: Non-allergist delivered PADL is supported by UK and World Health Organization guidelines but is not yet routine in UK hospitals. Understanding the views of healthcare workers (HCWs) on managing patients with penA records and exploring perspectives on delivering a PADL inpatient pathway are required to inform the development of non-allergist delivered PADL pathways. Objective: To explore the perspectives of non-allergist HCWs working in medical specialties on managing patients with penA records, and to explore the enablers and barriers to embedding PADL as a standard of care for inpatients. Methods: Semi-structured interviews with doctors, nurses, pharmacists and medicines optimization pharmacy technicians working in a district general hospital in the UK. Thematic analysis was used to analyse the data. Results: The PADL pathway was considered a shared responsibility of the multidisciplinary team, which needed to be structured and supported by a framework. PADL aligns with HCW roles but time to deliver PADL was a barrier. Training for HCWs on the benefits of PADL and delivering PADL for those patients where a penicillin might be beneficial during the current episode of care would both motivate HCWs to deliver PADL. Discussion and conclusion: The PADL pathway was acceptable to HCWs and aligned with their roles and current healthcare processes but their capacity to deliver PADL in a time pressured environment was a significant barrier.